Politics in Pre-Colonial Niger Delta: Reflections on the Role and Contributions of Women - Awortu, B. E.; Michael, B. T. (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
Women all over the world are active members of society who have contributed immensely to the growth and development of their societies. In the Niger Delta, women have contributed in no small measure to the political development of the region. This paper therefore examines politics in pre-colonial Niger Delta with a focus on the role and contributions of women. In the Niger Delta, women seem to have been deprived of some political privilege in the past due to the patriarchal nature of the society. However, some prominent female personalities in pre-colonial Niger Delta played significant role in the development of their societies. This study adopts the use of primary and secondary sources of data in generating the required data. The multi-disciplinary approach was used and knowledge from related disciplines enriched the available historical data. The study reveals that women in the Niger Delta were actively involved in politics. Some of them held chieftaincy titles, served as priestesses to deities, served in the military and above all discharged political duties in their communities. Women also made their political contributions by indirectly influencing their husbands and male relatives on important matters and decision making. However, women in pre-colonial Niger Delta politics were not granted equal political opportunities as their male counterparts which negatively impacted on the overall participation of women in politics. The study therefore recommends equal political opportunities for both male and female folks in the region and political consciousness on the part of women. Keywords: Women, Politics, Niger Delta, Pre-colonial